Uncertainty bands for inflation forecasts - Mårten Blix; Peter Sellin (Sveriges Riksbank, 1998)
The contribution of this paper is to show how the balance of risk for various macro variables can be linked to inflation uncertainty. Inflation uncertainty is derived from uncertainty in the macro variables that are deemed to be important for future inflation. The paper focuses on the technical derivation of inflation forecast skewness from uncertainty in such macro variables. The uncertainty in these macro variables is based on their historical standard deviations, but we allow these to be subjectively adjusted if there is reason to be more or less uncertain than historically. We also allow for a subjective assessment of the balance of risk, i.e. whether the distributions are symmetric or not. The baseline case is that the distributions of the macro-variables are symmetric and Gaussian with standard deviations based on historical data; any departures from the baseline can typically be justified from some indicator correlated with future inflation.
Keywords: C19; C53; E39; 330; Inflation forecast; inflation uncertainty; two-piece normal distribution; skewness